"It's necessary work": Stories of competitive youth sport coaches' developing critical praxes - Kramers, S.; Camiré, M. (The Sport Psychologist, 2024)
In this study, nine Canadian competitive youth sport coaches` challenges and successes in creating safer and more inclusive sport spaces were explored through individual pre- and postseason interviews and an in-season reflective portfolio of their coaching experiences. From a story analyst approach, the central narrative theme of "it`s my responsibility to enact change" was identified. A storyteller approach was then used to communicate the meanings of the central theme as accessible creative nonfiction composite stories: When is it okay to intervene?; burning out … it`s consuming me; and breaking through … it`s necessary work. Building on previous research, the findings demonstrate how coaches` critical praxes shift on a continuum of awareness and advocacy. The creative nonfictions may be used by coach educators and mental performance consultants to help coaches and leaders in sport assess their critical praxes toward challenging social issues in sport and acting in ways that support advocacy and empowerment.